Geochemistry of spinels from xenoliths of mantle lherzolites (sverre Volcano, spitsbergen Archipelago) - D. S. Ashikhmin; Yu.-S. Chen; S. G. Skublov; A. E. Mel'nik (Записки Горного института, 2017)
The paper presents the results of a study (LA-ICP-MS method) of spinel from the collection of mantle xenoliths of lherzolites (seven xenoliths) selected in quaternary alkaline basalts of the Sverre volcano, the Spitsbergen archipelago. The study of two large (more than 15 cm in diameter) xenoliths made it possible to study changes in the composition of minerals in the central, intermediate, and marginal parts of the samples of chromium diopside spinel lherzolites. The sinusoidal character of the REE distribution in spinels, which indicates the manifestation of mantle metasomatism, is established.